TREATMENT OF CONGENITAL UNDESCENDED SCAPULA WITH WOODWARD OPERATION, THE FUNCTIONAL AND COSMETIC OUTCOME (Iraqi Journal of Medical Sciences, 2016)
Background: Although congenitally undescended scapula (Sprengel’s deformity) reported to be rare, yet many families still seek medical help for their children. Cases with congenitally undescended scapula were collected, evaluated, and the majority subjected to surgical treatment with Woodward operation.Objective: Is to demonstrate the functional in addition to cosmetic improvements obtained with Woodward procedure used for Sprengel’s deformity. Methods: Between December 2007 and November 2009, fifteen patients with Sprengel deformity were evaluated (all have unilateral deformity) and treated surgically with Woodward procedure. The study included 9 males and 6 females, their age range from 5 to 11 years; right side is affected in 8 patients and left side in 7 patients. The preoperative grade of the deformity (according to Cavendish classification) and the maximum shoulder abduction were reported to assess severity and to be compared with the postoperative results.Results: All the patients get improvement in scapular elevation by about 2 grades and the increase in the maximum combined abduction was 20.33° in average. Two patients developed transient brachial plexus palsy. An omo-vertebral connection was found in 10 cases, in 3 cases the connection was bony, another 3 cases was cartilaginous, and 4 cases were fibrous. Conclusions: children with grade 2 and more and especially if abduction is much affected need to be treated with surgery, Woodward operation seems to be effective in handling both the cosmetic concern and the functional impairment. Keywords: Sprengel deformity, undescended scapula, Woodward.
Keywords: Sprengel deformity; undescended scapula; Woodward